Efficacy of voriconazole in a murine model of acute Trypanosoma cruzi infection - Gulin, Julián Ernesto Nicolás (2012)
OBJECTIVES: Antifungal triazole derivatives have been studied as possible alternatives for the treatment of Chagas' disease. Voriconazole has demonstrated in vitro activity against Trypanosoma cruzi, but its efficacy in vivo has not yet been tested. We aimed to determine the effect of voriconazole in a murine model of acute T. cruzi infection. METHODS: Treatment efficacy was evaluated by comparing parasitaemia, mortality and organ involvement (by histological examination) of infected mice. RESULTS: Treatment with voriconazole significantly lowered parasitaemia and mortality compared with controls, reduced the percentage of mice with amastigote nests in heart and skeletal muscle and moderately decreased myocardial inflammation. CONCLUSIONS: Our findings support the potential of voriconazole for the treatment of acute Chagas' disease and motivate future animal studies using varying doses and treatment schemes. Further evaluation of voriconazole for clinical use in human Chagas' patients is warranted.